Search for thermonuclear burst oscillations in the Swift/BAT data set - Li, Qing-Xin; Li, Zhaosheng; Pan, Yuan-Yue; Falanga, Maurizio (Frontiers in Astronomy and Space Sciences, 2024)
This study comprehensively analyzes type I X-ray bursts observed by Swift/BAT from 2005 to April 2024 to search for X-ray burst oscillations (XBOs) in neutron star low-mass X-ray binaries. XBOs, periodic signals detected within type I X-ray bursts, typically range from 11 to 620 Hz and are often observed in the soft X-ray data of these bursts. Using the high-sensitivity and precise timing capabilities of the Swift/BAT, we found 50 type I X-ray bursts from 37 neutron star low-mass X-ray binaries. We conducted a detailed timing analysis of these bursts. For sources with known burst oscillation frequencies, our findings largely corroborate previous studies. However, many sources displayed low confidence levels in the oscillation signals, with Z12 values between 10 and 20. For sources without known oscillation/spin frequencies, we utilized FFT analysis to search for signals across a broad frequency range. This approach revealed potential oscillation signals, with several bursts showing significance levels exceeding 3σ, including those from MAXI J1421–613, XTE J1701–407, XMM J174457–2850.3, Swift J1734.5–3027, IGR J17473–2721, Swift J174805.3–244637, Swift J181723.1–164300, and X 1832–330.